Perancangan Sistem Pembayaran Sekolah pada SMK ZZZ Menggunakan Metode Waterfall - Sugiyatno Sugiyatno (Neolectura, 2022)
The purpose of this research is to build a payment information system at one of the vocational schools in Bekasi. The problem is why the need for system development, because the payment process so far is still done conventionally which affects the service process takes longer. To build and develop the system using the waterfall method which is one of the system development methods known as the Software Development Life Cycle (SDLC). The stages of the waterfall method are communicating with the project owner in this case the school, planning needs by collecting data and analyzing, making a model of the software for data flow and control, functional processes, operating behavior and the information contained therein, coding in this case the researcher uses PHP (Hypertext Preprocessor) with a MySQL database and tests the system. There are 3 (three) actors in this application, namely Admin, Administrative Staff Officer and Students/guardians. Activities of this system include Payment of Tuition Fees, Manage Student Data, Manage Class Data, Manage Officer Data, Payment Transactions by Admin, Open Payment History, Reports.